Lewis Mayer, The Baltimore City Code: Comprising the Statutes and Ordinances Relating to the City of Baltimore 877 (1869) - (:unkn) unknown (My University, 1869)
§ 141: If any person shall fire or discharge any gun, pistol or firearms within the city, unless it be on some occasion of military parade, and then by order of some officer having the command, every such person, for every such offence, shall forfeit and pay a sum not exceeding five dollars; and if any gun, pistol or firearms shall be discharged from on board any vessel within the harbor of Baltimore, the captain of the vessel, as well as the offender, shall be liable to the said penalty.
Keywords: DISCHARGE